Availability of phosphorus in Ultisols by applying compost and phosphate rock - Jayadi, Muhammad; Rismaneswati, Rismaneswati; Majid, Sharini Abd (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2023)
Ultisols are the largest order in Indonesia among other acid soils, namely around 41,919 million ha, with the problem of insufficient P availability in soil for plant growth, requiring special treatment to increase available P in the soil. This study aims to examine the effect of compost and rock phosphate in increasing the availability of P in Ultisols. The research was conducted in April–May 2016 at the Laboratory of Chemistry and Soil Fertility, University of Hasanuddin, Makassar. The study used a randomized block design and was carried out by incubating straw compost, gamal leaves, cow dung and rock phosphate in Ultisol soil with a soil weight of 300 g. The research results show that 15th day of incubation showed the highest available P of 12.97 ppm with a pH of 5.15 in the KJ575%+KS525%+BF treatment, while on the 30th day of incubation the available P increased 17.45 ppm in the rock phosphate treatment with a pH of 5.58. The application of rock phosphate and SP36 reduced Al-P, Fe-P, and Ca-P, while the application of organic matter, in this case compost, did not reduce Al-P, Fe-P, and Ca-P.